2014
DOI: 10.1016/j.neuron.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Experience-Dependent Remodeling of Basket Cell Networks in the Dentate Gyrus

Abstract: SUMMARY The structural organization of neural circuits is strongly influenced by experience, but the underlying mechanisms are incompletely understood. We found that, in the developing dentate gyrus (DG), excitatory drive promotes the somatic innervation of principal granule cells (GCs) by parvalbumin (PV)-positive basket cells. By contrast, presynaptic differentiation of GCs and interneuron sub-types that inhibit GC dendrites is largely resistant to loss of glutamatergic neurotransmission. The networks of PV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(64 citation statements)
references
References 65 publications
3
61
0
Order By: Relevance
“…The appropriate targeting of entorhinal axons and granule cell (GC) mossy fibers was particularly evident when these projections were selectively tagged with membrane-bound GFP, expressed in a Cre-inducible manner from an AAV (AAVDJ DIO-mGFP) (Figures 2A–D and S5A–G). Staining for VGlut1 and a GC-enriched presynaptic protein, Synaptoporin (SPO) (Pieraut et al, 2014; Williams et al, 2011), showed that axons of release-deficient neurons formed abundant connections whose distribution across different axes also appeared normal (Figures 2E–G). These observations were not merely attributed to inefficient cleavage of Syb2 and/or silencing of release.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The appropriate targeting of entorhinal axons and granule cell (GC) mossy fibers was particularly evident when these projections were selectively tagged with membrane-bound GFP, expressed in a Cre-inducible manner from an AAV (AAVDJ DIO-mGFP) (Figures 2A–D and S5A–G). Staining for VGlut1 and a GC-enriched presynaptic protein, Synaptoporin (SPO) (Pieraut et al, 2014; Williams et al, 2011), showed that axons of release-deficient neurons formed abundant connections whose distribution across different axes also appeared normal (Figures 2E–G). These observations were not merely attributed to inefficient cleavage of Syb2 and/or silencing of release.…”
Section: Resultsmentioning
confidence: 99%
“…First, asymmetric contacts with vesicle pools have been found in cortices of Munc13 and Munc18 mouse mutants that completely lacked transmitter release in all neurons, albeit these mice could only be analyzed at birth, when connectivity in the forebrain is still rudimental (Varoqueaux et al, 2002; Verhage et al, 2000). Subsequently, exocytosis of neurotransmitter vesicles has been shown to be unnecessary for gross synaptic differentiation in vitro and in several neuron types in vivo (Deak et al, 2004; Harms and Craig, 2005; Imig et al, 2014; Lopez et al, 2012; Pieraut et al, 2014; Schoch et al, 2001; Shimojo et al, 2015; Yu et al, 2004; Zhang et al, 2008). Lastly, ionotropic glutamate receptors have been recently found to be dispensable for morphogenesis of dendritic trees and spines of pyramidal cells in the CA1 (Lu et al, 2013), although this conclusion was based on sparse gene knockouts, and the contribution of metabotropic receptor signaling could not be ruled out (Dore et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…and 9d n = 270, 1990 ± 32.47 a.u.). Recent studies showed that experiencedependent changes in the differentiation levels of PV+ interneurons in the mature hippocampus are involved in modulating structural plasticity and learning (Donato et al, 2013;Pieraut et al, 2014). Interestingly, a Nogo-A immunostaining could be observed within the almost totality of Parvalbumin (PV) positive interneurons both for CA1 and CA3 ( Figure 4B; 3 Nogo-A negative PV+ neurons were observed over a total of 360).…”
Section: Neuronal Nogo-a Expression In the Mouse Hippocampusmentioning
confidence: 91%
“…However, our data show a very strong expression of Nogo-A in Parvalbumin positive interneurons especially in the CA3 region of the hippocampus. It is noteworthy that recent studies describe a crucial role of PV + hippocampal interneurons in differentially modulating the distinct phases of hippocampus-dependent learning (Caroni et al, 2015;Donato et al, 2013) possibly via an activity-dependent increase in somatic innervation of principal granule cells by PV-positive basket cells of the dentate gyrus (Pieraut et al, 2014). Moreover, deletion of NgR1 has been shown to prevent the closure of the critical period for ocular dominance plasticity by regulating intralaminar connectivity of PV-positive neurons in the visual cortex (Stephany et al, 2014) and to improve fear memory extinction by regulating experience-dependent structural plasticity of the PV-positive network in the amygdala (Bhagat et al, 2015).…”
Section: Nogo-a Expression Within the Hippocampusmentioning
confidence: 99%
“…GABAergic inhibition controls spatiotemporal patterns of activity throughout many brain areas, and robust local GABAergic innervation of excitatory neurons is central for this role. Recent work in mammals has suggested that inhibitory connectivity is shaped by sensory experience, and identified activity-dependent transcriptional pathways important for this process (Morales et al, 2002;Chattopadhyaya et al, 2004;Jiao et al, 2006;Bloodgood et al, 2013;Pieraut et al, 2014). Despite these important advances, many aspects of inhibitory network development remain inadequately understood.…”
Section: Introductionmentioning
confidence: 99%